PENERAPAN METODE PEMBELAJARAN LATIHAN (DRILL) MENJAHIT MOZAIK DAN KOLASE UNTUK MENINGKATKAN KREATIVITAS DAN KEMAMPUAN KEWIRAUSAHAAN MAHASISWA PGSD UNIVERSITAS ISLAM BALITAR - Yudha Julistiyana, Maria Ulfa (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2019)
Mosaic and collage drill is an obligatory course at Primary School Teacher Education Department of Universitas Islam Balitar. However, the result of learning process is less optimum in its esthetic function. In addition to being unstable, the product of mosaic and collage has low price due to the use of things attached using glue. Therefore, learning process of mosaic and collage drill is an effort to enhance entrepreneurial skill of the students of Primary School Teacher Education at Universitas Islam Balitar. This research aims at describing the implementation of drill method to enhance the students’ entrepreneurial skill by improving creativity on mosaic and collage material. This research adopted qualitative approach. The type of research was Classroom Action Research. Findings revealed significant improvement at cycle 1 in the creation of mosaic, that is, 11.11%. Meanwhile, in the creation of collage was 16.66%. At cycle 2, the percentage of mosaic creation was 77.77%, while collage creation was 94.44%. Of 18 students, no one did not understand the preliminary materials of mosaic and collage. This finding suggests that the implementation of drill technique can enhance students’ entrepreneurial skill, creativity, and innovation in creation process especially the students of Primary School Teacher Education of Universitas Islam Balitar.